Complicated Diagnosis and Treatment of Giant Cell Arteritis: A Five-Year Follow-up - Lukauskaitė, Ieva; Valaikienė, Jurgita (Neurologijos seminarai, 2024)
A 68-year-old male started experiencing a localized headache in the left temporal region, which later spread to the right side. Initially, his symptoms were nonspecific; therefore, he visited several neurologists and was diagnosed with cephalgia. However, the symptoms progressed, the pain spread to the temporomandibular joints, and problems with chewing and swallowing developed. One month later, the patient noticed a subfebrile fever, as well as a severe headache and swelling of the eyes; consequently, he was admitted to the Department of Internal Medicine. An increased erythrocyte sedimentation rate and C-reactive protein were established. Color-coded duplex sonography revealed the concentric hypoechoic thickness of the walls in both superficial temporal arteries with increased blood flow velocities. The temporal arteries were very rigid and painful; therefore, it was difficult to perform an ultrasound examination. Subsequently, giant cell arteritis was diagnosed. The patient received an intravenous course of methylprednisolone, followed by prednisolone and methotrexate tablets.Five years later, the patient did not feel any pain or discomfort in the temporal area bilaterally at the follow-up visit. In control extracranial color-coded duplex sonography, the ‘halo’ sign was not observed, and the blood flow velocities were normal in both superficial temporal arteries. The ultrasound examination did not show signs of vasculitis.Every patient aged >50 years old with a new onset of headache and an increased erythrocyte sedimentation rate of ≥ 50 mm/h and/or high C-reactive protein levels should be checked for giant cell arteritis. Patients with giant cell arteritis should be monitored closely not only to prevent relapses but also to evaluate complications of treatment. Color-coded duplex sonography of superficial temporal arteries is an advantageous method not only for diagnosis but also for the monitoring of the disease. Raising awareness of giant cell arteritis is paramount and can help diagnose it in time.